ANALISIS STRATEGI PENANGANAN KELUHAN PELANGGAN PADA PT. PANAHMAS DWITAMA DISTRINDO - Evi Shofia Nandini; Moh. Agung Surianto (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
PT. Panahmas Dwitama Distrindo is a distribution company that is committed to providing the best service to consumers. PT Unilever Indonesia's main distributor company in the Jember and Probolinggo marketing areas has customers of more than five thousand shops and outlets to supermarkets. In the course of its business for two decades, the company received many complaints. The complaints include product availability, product defects, and delivery delays. This study aims to analyze the strategy for handling customer complaints by PT Panahmas Dwitama Distrindo. With a descriptive qualitative method, the authors conclude that the company accepts every complaint openly with many complaint channels, responsive and effective. Complaints received are immediately identified and submitted to management for a decision which is oriented towards customer satisfaction.